The Effect of Service Quality and Price on Customer Loyalty with Customer Satisfaction as an Intervening Variable (Case Study at Hotel Dedy Jaya Brebes) - Ariyani, Deva; Harini, Dwi; Setiadi, Roby; Syaifulloh, Muhammad (Universitas Mercu Buana, 2024)
The problem in this study is the decrease in demand for rooms at Hotel Dedy Jaya Brebes. The results of this study are a reference for the importance of maintaining customer loyalty, because the purpose of this study is to determine how the effect of service quality and price on customer loyalty, with customer satisfaction as an intervening variable. The research method used is a case study, which takes one particular object to be analyzed in depth by focusing on one problem. Purposive sampling technique on 86 people aged 17 years and over and have stayed or used the services of Hotel Dedy Jaya Brebes. Instrument tests are carried out with validity tests and reliability tests. This research was conducted with a Structural Equation Model (SEM) approach using Partial Least Square (PLS) software. The results showed that service quality affects customer satisfaction; price affects customer satisfaction; service quality affects customer loyalty; price affects customer loyalty; and customer satisfaction affects customer loyalty. The variable contribution of service quality and price to customer satisfaction is 75.4%, while service quality and price to customer loyalty is 82.6%. By conducting this research, it is hoped that there will be an improvement in the quality of service and prices offered by Hotel Dedy Jaya Brebes to its customers.